2009
DOI: 10.1024/1012-5302.22.4.254
|View full text |Cite
|
Sign up to set email alerts
|

Psychosoziale Interventionen für Paare, die mit einer Krebserkrankung leben. Eine Literaturübersicht

Abstract: Couples experience cancer as a dyad. Step by step, they have to learn to integrate the illness into their lives. It can be assumed that psychosocial nursing interventions would offer them helpful support. Yet, there is no evidence showing which interventions are the most effective in supporting the couple in the illness management. This literature review was undertaken to explore this issue and was guided by following questions: 1) What kind of psychosocial intervention programmes exist for couples experiencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…cooking, doing the dishes, cleaning the apartment, administrative issues). Literature also describes relatives as an important and supportive part in the lives of patients with a chronic condition [27,39,48]. Our results are consistent with that evidence.…”
Section: Discussionsupporting
confidence: 91%
“…cooking, doing the dishes, cleaning the apartment, administrative issues). Literature also describes relatives as an important and supportive part in the lives of patients with a chronic condition [27,39,48]. Our results are consistent with that evidence.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, providing support and understanding symptom management process could be pivotal in improving the quality of life of those sufferers [ 89 ]. Literature describes relatives as an important and supportive part in the lives of patients with a chronic condition ([ 29 , 71 , 90 ]; Stadtmann MP, Maercker A, Binder J, Schnepp W: Why do I have to suffer? Symptom management, views and experiences of persons with a CPTSD: A grounded theory approach, submitted).…”
Section: Discussionmentioning
confidence: 99%
“…In general, as informal social support, patients’ relatives play a significant and vital role in research on symptom management [ 29 33 ]. Relatives of those affected by a chronic mental illness such as CPTSD support them in several ways.…”
Section: Introductionmentioning
confidence: 99%
“…No study was found that dealt with symptom management in the everyday life of adult patients with CPTSD. Patients’ relatives play a significant role in research on caregivers and symptom management [ 19 22 ]. The relatives can be both a facilitator and a barrier to patients’ symptom management [ 16 , 23 ].…”
Section: Introductionmentioning
confidence: 99%